Mesostructured Electroactive Thin Films Through Layer‐by‐Layer Assembly of Redox Surfactants and Polyelectrolytes. Issue 8 (1st July 2020) - Piccinini, Esteban; Ceolín, Marcelo; Battaglini, Fernando; Azzaroni, Omar
Abstract : The Cover Feature shows a 2D hexagonal mesostructured electroactive film obtained through layer‐by‐layer assembly of (ferrocenylmethyl)hexadecyldimethylammonium bromide, a redox surfactant, and poly(acrylic acid). The picture also includes an experimental GISAXS pattern of the mesostructured film. By using ferrocene‐appended surfactants as structural and functional units, the formation of robust electroactive mesostructured films can be achieved. More information can be found in the Communication by O. Azzaroni, F. Battaglini, and co‐workers (DOI: 10.1002/cplu.202000358 ).